THE BUILDING OF THE BALANCED SCORECARD FOR ACADEMICAL ENVIRONMENTS: APPLICATION IN A GERMAN ACADEMIC UNIT - Walter, Fábio; Gasparetto, Valdirene; Neto, Francisco José Kliemann (Anais do Congresso Brasileiro de Custos - ABC)
Many publications are reporting, in the last years, the benefits of the Balanced Scorecard (BSC) implantation in several types of organizations. However, few texts offer methodologies for the building and implantation of the system, that should be adapted to each context. So, the present article intends to collaborate with the literature, proposing a methodology for using the BSC in academic environments, and offering the report of a BSC building in an academic unit of a German university, where the development was based on this proposal. The article describes the reached results, from the process of strategic discussion to the developed steps for the building. In the end are presented conclusions and criticism to the reached results.